GREEN APPROACH TO SYNTHESIS, CHARACTERIZATION OF SILVER NANOPARTICLES BY USING TRIDAX PROCUMBENS LEAF EXTRACT AND THEIR ANTIBACTERIAL ACTIVITY (International Journal of Food and Nutritional Sciences, 2022)
In the last few years, it has been seen that the importance of silver nanoparticles has gained much interest by many chemists and biologists. Therefore, Indian medicinal plants has yet to bring numerous sources of profitable, healthy, mostly reduced and stabilized compounds utilized in the biosynthesis of silver nanoparticle. The main aim of this study is to investigate the viable and sustainable ways for the biosynthesis of AgNPs from 1 mM aqueous AgNO3 using leaf extracts of widely available plants such as Tridax procumbens (Tridax), which are well known for their wide availability and medicinal property. AgNPs were synthesized by the reaction of 1 mM AgNO3 and 5% leaf extracts of each plant separately. The formations of the AgNPs were confirmed by the colour changes of the mixture solution and duly characterized by UV-Visible spectrophotometric analysis. The synthesized silver nanoparticles were subjected to Ultraviolet-Visible (UV-Vis) Spectroscopy, Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscope (SEM), their antibacterial and antifungal activities were tested against two bacterial strains and one fungal strain. Finally, the AgNPs showing better antimicrobial activity was tested for their water disinfection study against three water samples collected from River, Pond and Cannel. Obtained AgNPs from the different leaf extracts indicated higher antimicrobial activities against Escherichia coli and Bacillus spp. in comparison to both AgNO3 and the raw plant extracts of Tridax. The final results showed that Tridax extract silver nanoparticles are showing significant antimicrobial activities, So the bacterial inhibition zone by the silver nanoparticles prepared from the Tridax leaves extract show maximum inhibition for Gram +ve S. aureus and K. Pnemoniae and Gram negative E. coli as well as A. niger.